Clinicopathological Characteristics of Primary Appendiceal Mucinous Neoplasm and Recurrence After Radical Resection - Wang, Zaibiao; Yin, Manman; Shao, Jiayun; Yin, Zhipeng; Peng, Jie; Lu, Zhengmao (Frontiers in Surgery, 2022)
Objective: Appendiceal mucinous neoplasm (AMN) is a rare obstructive dilatation of the appendix caused by intraluminal accumulation of mucoid material, showing an insidious onset and few specific clinical manifestations. The purpose of the study is to analyze clinicopathological characteristics of primary AMN and recurrence after radical resection. Methods: A total of 50 patients were included in the retrospective cohort study of AMN. Patient data, including demographics, tumor characteristics, surgical management, preoperative serum CEA and CA19-9 levels were collected. All patients were followed-up with interval CT scans till the end of December 2021, with overall survival (OS) and progression-free survival (PFS) calculated. Results: All patients were confirmed as AMN by pathological diagnosis after surgery, including 28 cases (56.00%) of LAMN and 22 cases (44.00%) of non-LAMN. Among 50 AMN patients, there were 12 cases (24.00%) complicated with PMP. Higher proportions of patients with pTis, pT3, pT4a, ruptured at presentation, and PMP were found in non-LAMN patients than LAMN patients (P < 0.05). There was remarkable difference with regard to preoperative serum CA19-9 levels between LAMN and non-LAMN patients (P = 0.044). A higher proportion of patients with ruptured at presentation was found in patients complicated with PMP than those not (P < 0.001). The patients with PMP had increased tumor size compared with those without (P = 0.031). Remarkable differences were observed in terms of preoperative serum CA19-9 (P = 0.009) levels between patients with PMP and without. We performed multivariate analysis of the presence or absence of PMP and found that ruptured at presentation was found as risk factors of PMP in AMN patients (P = 0.003). The PFS in the patients with PMP and those without was 33.33% (4/12) and 2.63% (1/38), showing a significant difference (P = 0.002). Conclusion: The study demonstrates that ruptured at presentation and PMP may influence the prognosis and survival of AMN patients.